Emission of Inorganic PM10 during the Combustion of Spent Biomass from Mallee Leaf Steam Distillation - Gao, Xiangpeng; Yani, S.; Wu, Hongwei (American Chemical Society, 2015)
A mallee leaf (~1 cm long × ~1 cm wide), termed as “raw leaf”, was distilled in steam for 60 min to extract essential oil (mainly 1,8-cineole) and prepare a spent leaf. The raw and spent leaf samples were size-reduced and sieved to 75-150 µm to prepare samples for combustion in a laboratory-scale drop-tube furnace at 1400 °C in air to investigate the effect of steam distillation on the emission behavior of inorganic particulate matter with an aerodynamic diameter of <10 µm (PM10). The results show that steam distillation has little effect on the yields of PM1 and the sum of Na, K, and Cl in PM1. However, it leads to considerable reductions in the yields of PM1-10 and its key forming elements (Mg and Ca). The reduction in the PM1-10 yield is another advantage of using the spent leaf as combustion feedstock, in addition to the extraction of 1,8-cineole as a value added product.